Adaptation to climatic change and variability: some response options to agricultural production in Uruguay - Giménez, Agustín; Lanfranco, Bruno (Revista Mexicana de Ciencias Agrícolas, 2018)
Adaptation to climatic change and variability: “some response options to agricultural production in Uruguay”. Like is mentioned in several reports of Intergovernmental Panel about Climatic Change (IPCC, 2007a; IPCC, 2007b), the international scientific community express that increase of greenhouse effect gas concentration has extreme changes in daily, seasonal, between years and along decades climatic variability. Climatic variability and occurrence of extreme events (frost, hail, droughts) results in very important damages for agricultural sector and is very frequent that this sector requires several years to economically and financially recover from such damages. The Agricultural Weather and Information Systems unit (GRAS) from National Institute of Agricultural Research (INIA) from Uruguay together with World Bank (BM) and Cornell University (CU) from United States of America, ended in year 2009 the project “Vulnerability to climatic change in agricultural production systems in Latin America and Caribbean: development of responses and strategies” (Giménez and Lanfranco, 2009). The aim of proposal was to outline an action plan with recommendations for development of responses and strategies with the purpose to contribute with a better adaptation to climatic variability impacts and occurrence of extreme climatic events in Uruguay’s agricultural production systems. The outcome of the work was identification and giving priority 3 response options: system of information and support for decision making; water management; and insurance and other finance products for risk management.
Keywords: adaptation; climatic change; response options; agricultural production